Suatu Tinjauan Mengenai Penerapan Strategi Outsourcing dan Strategi Core Competency Studi Kasus pada Starbuck - Erna . (Jurnal Akuntansi, 2007)
in the new landscape, the resources, capabilities, and core competencies in the firm 's internal environment may have a relatively stronger influence on its performance than doconditions in the external environment. Firms must exploit their current advantages while simultaneously using their resources and capabilities to form new advantages that can leadto competitive success in future. By studvmg their skills relative to those associated with primary and support activities, firms can understand their cost structure and identify theactivities through which they can create value. When the firm cannot create value in either a primary or support activity, outsourcing is considered. Used commonly in the globaleconomy, outsourcing is the purchase of a value-creating activity from an external supplier. The firm must outsource only to companies possessing a competitive advantage in terms ofthe particular primary or support activity under consideration. In addition, the firm must continuously verify that it is not outsourcing activities from which it could create value.Keywords: outsourcing strategies, core competencies strategies